Assessment of Health Risks in Wheat Crop Irrigated by Manka Canal, Dera Ghazi Khan, Pakistan - Muhammad Anwar ul Hassan; Sabiha Javied; Umair Riaz; Muneera A. Saleh; Khalid H. Alamer; Naila Siddique; Ambreen Aslam; Nabeela Noor; Qamar uz Zaman (Applied and Environmental Soil Science)
Background. Manka canal’s metal concentration rises from human activities’ garbage. Untreated water from the canal is used by farmers for local crop irrigation. Immediate action is crucial to assess heavy metal levels and ensure soil suitability for agriculture as metal pollution persists. Purpose. The current study was conducted to assess the health risks associated with metal pollution at Manka Canal, Dera Ghazi Khan. Methods. A total of eighty-four wastewater, soil, and wheat samples were collected from study areas. The collected samples were analyzed for heavy metals (Cd, Cu, Fe, Mn, Ni, Pb, and Zn) using a flame atomic absorption spectrometer (FAAS). Results. The significant findings of the study revealed that the concentration of heavy metals in most of the collected samples of soil, water, and wheat was above the World Health Organization (WHO) permissible limits. The mean concentrations of Cd, Cu, Mn, Ni, Pb, and Zn were at relatively higher concentrations, i.e., 4.88, 22.03, 38.2, 89.2, 19.62, and 67.9 mg/kg, respectively, in collected wheat samples. The soil and irrigation water quality metrics had values that exceeded the acceptable thresholds, rendering them unfit for agricultural use. The local community faces an elevated health risk index for both children and adults due to the consumption of wheat crop as HRI is greater than 1 for nonessential elements like Cd and Pb. Conclusion. The study suggested that wastewater irrigation leads to the accumulation of heavy metals in foodstuffs, causing potential health risks to consumers. The gradual accumulation of these contaminants in biological systems finally gives rise to severe health-related issues. Therefore, it is crucial to implement robust wastewater treatment processes and stringent quality control measures to minimize health risks associated with the consumption of crops grown using reclaimed water. Prior to irrigating crops like wheat and vegetables, it is strongly advised to treat municipal wastewater to prevent soil and dietary toxicity from heavy metals.